Vocational training. Present and future - Menéndez, José (Razón y fe, 2018)
For various reasons, Vocational Training continues to constitute a serious problem in Spain. This article, after reviewing the various laws of Education, postulates a better integration of professional training within our educational system and a better relationship with the world of industry and business. Getting it right or not is  essential to get out of the crisis.